ANALISIS KELENGKAPAN IMUNISASI DASAR DI WILAYAH KERJA PUSKESMAS LEMO KABUPATEN BARITO UTARA - Achmad Rizal; Agus Jalpi (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2020)
Healthy behaviour is a proactive attitude to maintain and improve health, prevent the risk of disease, protect yourself from disease threats and play an active role in public health movement activities. One of the healthy attitudes that must be created is the attitude of prevention and disease management with immunization activities. This research aims to analyse the relationship level of education, knowledge and attitude of baby mothers with the completeness of basic immunization in the work area of Puskesmas Lemo Teweh District of North Barito Regency. The method used is an analytical survey with a Cross Sectional approach aimed at knowing the relationship level of education, knowledge, attitude with immunization in the baby. The result is a relationship between knowledge and attitude with the completeness of immunization in infants, completeness of basic immunization in infants 48.4% (31 babies). To increase the percentage of completeness of basic immunization in Lemo Puskesmas is by improving the extension, especially about the benefits and schedule of immunization administration.